Application of Structural-Functional Theory in Risk of HIV Transmission - Karki, Tej Bahadur; Gartoulla, Ritu Prasad (Journal of Advanced Academic Research, 2017)
The study was conducted with the purpose to explore the interrelationship and interdependency between the individual and whole social systems that effects on HIV transmission during the time of social changes and transformation. The concept of structural functional theory was adopted to conduct this study. Phenomenological approach was applied to explore the experiences of risk behavior of human immune deficiency virus (HIV) transmission among the respondents working in Kathmandu valley (Kathmandu, Lalitpur and Bhaktpur districts). This Research was based on exploratory research design and simple random technique was used to select the respondents. The Study was conducted in Kathmandu valley among garment factory workers, brick factory workers, transport workers and health workers. Individual factors, socio-cultural factors, economic factors, educational factors and political factors are found as a functional unit of society which functions to influence the risk of HIV transmission in whole social structure. So, the finding is individual should be aware on the negative function of factors which can influence to increase the risk of HIV transmission. Cultural practices should be open to discuss about the risk behavior of people regarding their connection with HIV transmission.